The Shift of Students Attitudes Towards the Teacher of Physical Education - Jurgita Čepelionienė; Vida Ivaškienė (Lithuanian Sports University, 2018)
Background. The aim of the research was to identify the shift of the attitude of students towards the physical education  teacher.  Hypothesis  of  the  research:  Students  attending  compulsory  physical  education  classes  view physical education teacher worse than those who have a possibility of physical education as an optional subject at the university. Methods. The first study was conducted in the spring semester of 2009 and the second study was conducted after four years (in the spring semester of 2013). First year students took part in the research, 362 females participated in the first study and 343 females in the second study. The total number of male participants in the first study was 129, in the second study - 169. Research participants were students selected from several universities using convenience sampling strategy. The data were analysed using the statistical data software package SPSS 21.0 for Windows. Results. The analysis of the research data about the most appealing traits of physical education teacher revealed that male students appreciated the teacher's ability to be calm, interested in each student, to be creative and be able to apply innovations. Conclusions. For students the most appealing traits of physical education teachers are good knowledge of the subject and friendliness. The female students also emphasized the importance of good appearance of the teacher of physical education as well as good interaction with the group, the male students appreciated a good sense of humour and possibility of easy communication with the teacher. In four years' time students' attitudes towards the teacher of physical education improved. Keywords: students' attitudes, physical education teacher, university physical education.